Depositional age and provenance of the Cobar Supergroup - Parrish, M.; Collins, Bill; Hegarty, R.; Gilmore, P.; Huang, H. (Taylor & Francis Co Ltd, 2018)
© 2018, © 2018 Geological Society of Australia. The turbidite-filled, Lower Devonian Cobar Basin is characterised through a detrital zircon study. Uranium–Pb age data for six samples were combined with published data to show the basin has a unique age spectrum characterised by a subordinate Middle Ordovician (ca 470 Ma) peak superimposed on a dominant ca 500 Ma peak. Maximum depositional ages for 3 samples were ca 425 Ma, close to the published Lower Devonian (Lochkovian 419–411 Ma) biostratigraphic ages. A minor ca 1000 Ma zircon population was also identified. The major source of the 500 Ma zircons was probably the local Ordovician metasedimentary basement, which was folded, thickened and presumably exposed during the ca 440 Ma Benambran Orogeny. The ca 470 Ma age peak reflects derivation from Middle Ordovician (Phase 2) rocks of the Macquarie Arc to the east. The I-type Florida Volcanics, located ~50 km eastward from the Cobar Basin, contains distinctive Middle and Late Ordovician zircon populations, considered to be derived from deeply underthrust Macquarie Arc crust. Protracted silicic magmatism occurred before, during and after Cobar Basin deposition, indicating that the basin formed by subduction-related processes in a back-arc setting, rather than as a continental rift.